Expression of activin A in liver tissue and the outcome of patients with biliary atresia - Džepina, Petra; Ćorić, Marijana; Kovačić Perica, Matea; Aničić, Mirna Natalija; Grizelj, Ruža; Vuković, Jurica (Frontiers in Pediatrics, 2024)
Biliary atresia (BA) is a rare disease of unknown etiology which leads to cirrhosis and death if left untreated. The standard of care is early hepatoportoenterostomy (HPE). Long-term follow-up is mandatory, during which most patients will require liver transplant. Activin A belongs to the transforming growth factor-ß (TGF-ß) superfamily. TGF-ß is a central regulator in chronic liver disease. We have studied the expression of activin A in liver tissue collected intraoperatively during the HPE. We included patients who underwent HPE in a single medical center. Clinical, ultrasonographic, and pathohistological data were collected. Activin A immunostaining was performed. Expression in bile duct epithelium and hepatocytes was scored as weakly positive, moderately positive, and strongly positive. Patients were then divided into 3 groups accordingly. We observed the outcome after HPE at 3 months, 2 years and at the end of follow-up. The study encompassed 37 patients. At 3 months after HPE, 92.3% with weakly positive reaction on activin A (group A) achieved good jaundice clearance, whereas only 44.4% with moderately (group B) and 40% with strongly positive reaction (group C) achieved good jaundice clearance (p=0.008). Two years after HPE, 92.3% in group A survived with native liver (SNL), but only 33.3% in group B and 46.7% in group C had SNL (p=0.007). At the end of follow-up, 83.3% in group A survived with native liver, as well as 33.3% in group B and 40% in group C. Activin A is a valuable pathohistological predictor of the outcome of BA after HPE.